PENDIDIKAN ISLAM MULTIKULTURAL DALAM PERSPEKTIF FILOSOFIS - Ma’mun Mu'min (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2016)
Since the years 1950 of multicultural education discourse. The reason involves the issue of racism and discrimination against minority groups originating from Africa. 1970s discourse becomes stronger, such as in America, England, Germany, and others. 1980 is seen as the beginning of the emergence of multicultural educational institutions, as initiated by James A Banks et al. The idea of multicultural education is gaining momentum globally as recommended UNISCO in October 1994 in Geneva Switzerland. Among mulikultural educational thinkers of the West, like James A Banks, L. Derman-Sparks, Dawn Gill, Geneva Gay, Christine Sleeter, Peter McLaren, Donna M. Gollnick, Philip Chinn, Will Kymlica, G. Shin and P. Gorski,. Islamic thinkers who carries a lot of Islamic education multicultural issues, such as Fazlur Rahman,